Design of a passive constant-force mechanism based on a five-bar mechanism. (January 2020) - Xie, Qizhi; Liu, Songyong; Jiang, Hongxiang
Highlights: A five-bar constant-force mechanism (FB-CFM) is proposed. Rotating cams are used to avoid the stuck phenomenon of moving pair. Tension springs are directly connected with the top of the two cams. The FB-CFM is compact and can be installed in narrow and long spaces. Abstract: To solve the problem of complex control of an active constant-force mechanism (CFM) and the large radial dimension of a passive CFM, a new type of CFM based on a two-degree-of-freedom five-bar mechanism (FBM) is proposed in this paper, which is called FB-CFM. Its constant force can be realised by superposition of the negative-stiffness mechanism (NSM) and positive-stiffness mechanism (PSM), and the constant-force range can be adjusted by the PSM. The NSM is designed by adding cams and tension springs on the basis of the FBM and has a compact structure. The tension spring moves in parallel and extends when the FBM operates, which produces negative stiffness. The mathematical model of the FB-CFM is simple and accurate, which does not require complicated calculation of flexible body. To verify the feasibility of the research results, the output characteristic of the FB-CFM was tested by simulation and experiment. The results show that the FB-CFM can produce a relatively stable constant force at low-velocity, which provides a basis for the structural design and theoretical research of compact CFMs.